A Built-In Self-Repair With Maximum Fault Collection and Fast Analysis Method for HBM - Yoon, Joonsik; Lee, Hayoung; Moon, Youngki; Shin, Seung Ho; Kang, Sungho (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems, 2024)
High Bandwidth Memory (HBM) represents a significant advancement in memory technology, requiring quick and accurate data processing. Built-in self-repair (BISR) is crucial for ensuring high-capacity and reliable memories, as it automatically detects and repairs faults within memory systems, preventing data loss and enhancing overall memory reliability. The proposed BISR aims to enhance the repair rate and reliability by using a content-addressable memory structure that operates effectively in both offline and online modes. Furthermore, a new redundancy analysis algorithm reduces both analysis time and area overhead by converting fault information into a matrix format and focusing on fault-free areas for each repair solution. Experimental results demonstrate that the proposed BISR improves repair rates and derives a final repair solution immediately after the test sequences are completed. Moreover, hardware comparisons have shown that the proposed approach reduces the area overhead as memory size increases. Consequently, the proposed BISR enhances the overall performance of BISR and the reliability of HBM.
Keywords: Analysis time; Bandwidth memory; Build-in redundancy analyze; Build-in self-repair; Built-in redundancy analysis; Builtin self repairs; Content-addressable memory; High bandwidth; Repair rate; Analysis time; built-in redundancy analysis (BIRA); built-in self-repair (BISR); content-addressable memory (CAM); repair rate